1995
DOI: 10.1111/j.1752-1688.1995.tb03426.x
|View full text |Cite
|
Sign up to set email alerts
|

CLIMATE, SNOW COVER, GLACIERS, AND RUNOFF IN THE TIEN SHAN, CENTRAL ASIA1

Abstract: The Pica Shan, a mountainous region located on the northern periphery of central Asia, has a wide range of climatic and hydrological conditions. On the basis of long term data from 348 meteorological and glaciological stations, the annual distribution of precipitation in different regions and elevational zones of the Tien Shan was calculated. Major climatic features are the entrance of moisture during spring‐summer, small winter precipitation, decrease of precipitation towards the east and the center of the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
149
1
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(156 citation statements)
references
References 0 publications
5
149
1
1
Order By: Relevance
“…This observation is in line with the mass balance sensitivities of the glaciers in Central Asia as inferred by Rasmussen (2013). The observed cumulative mass balance determined by the glaciological method is supported by several remote sensing studies underlining the findings (Aizen et al, 1995b;Bolch et al, 2011Bolch et al, , 2012Pieczonka et al, 2013;Gardelle et al, 2013;Pieczonka and Bolch, 2015;Kronenberg et al, 2016).…”
Section: Summary Of Glacier Length and Mass Changes In Central Asiasupporting
confidence: 70%
See 1 more Smart Citation
“…This observation is in line with the mass balance sensitivities of the glaciers in Central Asia as inferred by Rasmussen (2013). The observed cumulative mass balance determined by the glaciological method is supported by several remote sensing studies underlining the findings (Aizen et al, 1995b;Bolch et al, 2011Bolch et al, , 2012Pieczonka et al, 2013;Gardelle et al, 2013;Pieczonka and Bolch, 2015;Kronenberg et al, 2016).…”
Section: Summary Of Glacier Length and Mass Changes In Central Asiasupporting
confidence: 70%
“…There has been an extensive network of continuous long-term meteorological time series of air temperature and precipitation in Central Asian countries during the Soviet Union times (Aizen et al, 1995b). However, this network thinned out considerably during the recent past .…”
Section: Meteorological Measurementsmentioning
confidence: 99%
“…The value for dT/dz. corresponds to the average monthly lapse rate for which melt is expected for the Central Tien Shan published in Aizen et al (1995). The lapse rate is held constant.…”
Section: Model-based Extrapolation To Determine Glacier-wide Mass Balmentioning
confidence: 99%
“…Daily precipitation totals and daily mean temperatures are calculated for the use as model input. Monthly temperature lapse rates calculated by Aizen et al (1995) from six stations in the Central Tien Shan are used to extrapolate the temperature data to the mean glacier elevation (Kronenberg et al, 2016).…”
Section: Study Area and Datamentioning
confidence: 99%
“…Air temperature correlates well with several energy balance components, hence it is the most commonly used index, but other variables such as net radiation, wind speed, vapour pressure and solar radiation are also used. Studies have shown that temperature index or degree-day models are the most widely used approaches for runoff computation from glacierized basins (Aizen et al, 1995;Rango & Martinec, 1995;Semadeni-Davies, 1997;Hock, 2003).…”
Section: Introductionmentioning
confidence: 99%